PENGEMBANGAN PEMBELAJARAN BERBASIS MEDIA POWERPOINT DALAM PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Syarifah Aini (LPPM Universitas Bina Bangsa, 2022)
This study aims to develop learning media based on Information and Communication Technology (ICT), especially PowerPoint, for integrated thematic learning with the theme of energy saving, in the energy and motion subtheme. The method used is research and development, and one of the important procedures is the validation of PowerPoint-based learning media. Qualitative validity was carried out on 41 fourth-grade teachers in the city of Medan, North Sumatra, and the results showed that the media had good quality. The media was then tested on 32 fourth-grade students of a public elementary school in Medan, North Sumatra. The results showed that there was a significant increase in student learning outcomes from 68.94 to 76.72. In addition, powerpoint-based learning media has a positive effect on students, and where they feel very happy when using it